KEMAMPUAN KOMUNIKASI MATEMATIKA MAHASISWA DITINJAU DARI CARA KERJA OTAK YANG DOMINAN - Nursupiamin Nursupiamin (Koordinat Jurnal MIPA, 2020)
The study of student's mathematical communication skills in terms of the workings of the dominant brain aims to see the mathematical communication skills of students who are dominant right brain and students who are dominant left brain. This type of research is quantitative descriptive with 18 research subjects who are students of Mathematics Tadris who program Linear Algebra. Data collection techniques used are the provision of characteristic identification tests and tests of mathematical communication skills. The results of the study indicate descriptively that the written communication of the right brain dominant group is better than the left brain group and the oral communication of the left brain dominant group is better than the right brain group.